Assessment of the Anti-adipogenic Effect of Crateva religiosa Bark Extract for Molecular Regulation of Adipogenesis: In Silico and In Vitro Approaches for Management of Hyperlipidemia Through the 3T3-L1 Cell Line - Singh, Monika; Sachdeva, Monika; Kumar, Nitin (Current Pharmaceutical Biotechnology, 2025)
Aims This study aimed to determine the phytoconstituents of Crateva religiosa bark (CRB) and evaluate the hypolipidemic effect of bioactive CRB extract by preventing adipocyte differentiation and lipogenesis. Background After performing the preliminary phytochemicals screening, the antioxidant activity of CRB extracts was determined through a DPPH (2, 2-diphenyl-1-picrylhydrazyl) assay. Ethyl acetate extract (CREAE) and ethanol extract (CRETE) of CRB were selected for chromatographic evaluation. Methods The antihyperlipidemic potential was analyzed by molecular docking through the PKCMS software platform. Further, a 3T3-L1 cell line study via in vitro sulforhodamine B assay and western blotting was performed to confirm the prevention of adipocyte differentiation and lipogenesis Results The total phenolic contents in CREAE and CRETE were estimated as 29.47 and 81.19 μg/mg equivalent to gallic acid, respectively. The total flavonoid content was found to be 8.78 and 49.08 μg/mg, equivalent to quercetin in CREAE and CRETE, respectively. CRETE exhibited greater scavenging activity with the IC50 value of 61.05 µg/ mL. GC-MS analysis confirmed the presence of three bioactive molecules, stigmasterol, gamma sitosterol, and lupeol, in CRETE. Molecular docking studies predicted that the bioactive molecules interact with HMG-CoA reductase, PPARγ, and CCAAT/EBP, which are responsible for lipid metabolism. In vitro, Sulforhodamine B assays revealed that CRETE dose-dependently reduced cell differentiation and viability. Cellular staining using ‘Oil Red O’ revealed a decreased lipid content in the CRETE-treated cell lines. CRETE significantly inhibited the induction of PPARγ and CCAAT/EBP expression, as determined through protein expression via western blotting. Conclusion The influence of CRETE on lipid metabolism in 3T3-L1 cells is potentially suggesting a new approach to managing hyperlipidemia.
Keywords: in vitro